ANALISIS BELT AND ROAD INITIATIVE SEBAGAI STRATEGI GEOPOLITIK TIONGKOK DI EROPA TAHUN 2017-2022 - Siti Zaimatun Nabila; Mhd. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research analyzes how China implements Belt and Road Initiative as its geopolitical strategy in Europe. Since its launched, Belt and Road Initiative has been known and promoted as China's most ambitious foreign policy with a main focus on infrastructure development within global scope. Europe as a developed region is also became one of China's BRI targets, because it has the capability to support the reviving of China's economy which is uneven in its certain area. Even though Europe later launched the Global Gateway Strategy with a similar vision to BRI, it was not immediately able to replace China's BRI position or even disrupt China's relations with European countries. Until 2022, BRI projects still exists and contribute significantly to China's economy, as well as China's geopolitical developments in Europe. The perspective used in this study is realism along with geopolitical theory. Based on the assumption of the perspective and the theory, China, through the Belt and Road Initiative, seeks domestic prosperity while simultaneously developing its geopolitical reach in the European region. 25 European countries have signed MoUs related to the Belt and Road Initiative, yet its implementation is not limited to these 25 countries, especially the Silk Road Economic Belt which continues to be improved throughout Europe including the landlocked countries. Keywords: Belt and Road Initiative, Geopolitics, Infrastructure Development